2020
DOI: 10.3390/genes11020152
|View full text |Cite
|
Sign up to set email alerts
|

Genetic and Genomic Tools in Sunflower Breeding for Broomrape Resistance

Abstract: Broomrape is a root parasitic plant causing yield losses in sunflower production. Since sunflower is an important oil crop, the development of broomrape-resistant hybrids is the prime breeding objective. Using conventional plant breeding methods, breeders have identified resistant genes and developed a number of hybrids resistant to broomrape, adapted to different growing regions worldwide. However, the spread of broomrape into new countries and the development of new and more virulent races have been noted in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 68 publications
0
24
0
Order By: Relevance
“…The accelerated progress in the genomic and biotechnological research currently happening in pea [34,62,63], will soon facilitate gene discovery and the development of breeder's friendly molecular markers allowing efficient marker assisted selection, as has already been achieved in sunflower breeding for O. cumana resistance [64]. We are hungry to apply these developments into pea breeding for O. crenata resistance.…”
Section: Discussionmentioning
confidence: 99%
“…The accelerated progress in the genomic and biotechnological research currently happening in pea [34,62,63], will soon facilitate gene discovery and the development of breeder's friendly molecular markers allowing efficient marker assisted selection, as has already been achieved in sunflower breeding for O. cumana resistance [64]. We are hungry to apply these developments into pea breeding for O. crenata resistance.…”
Section: Discussionmentioning
confidence: 99%
“…Vertical resistances are mainly governed by major genes that have a gene-for-gene relationship with a pathogen avirulence factor, thus generating a hypersensitive response (HR) to a specific race and most often preventing the development of the pathogen. Although their use is fairly simple, the history of O. cumana parasitizing sunflower specifically is remarkable [ 197 ]. Indeed, this example has shown that the resistances thus successively generated are unfortunately not sustainable.…”
Section: Strategies For Effective Parasitic Weed Managementmentioning
confidence: 99%
“…Several resistant hybrids have been developed to reduce yield losses due to the parasitic plants through conventional breeding methods of phenotypic screening and selection (Cvejić et al, 2020). The genomic tools may be further exploited to identify resistance genes and subsequent introduction in elite inbred lines, particularly to pyramid resistance and discourage evolution of new virulence types (Cvejić et al, 2020). SSR markers from LG3 showed strong association with various resistance genes i.e.…”
Section: Broomrape Resistance (Orobanche Spp)mentioning
confidence: 99%